Prediction of the daily share price fluctuations of SURAMINV. A neural netword model (2019)
As opposed to the weak form of efficient-market hypothesis, the current study shows that it is possible to do good predictions about the daily share price fluctuations of Suraminv, using artificial neural network models. Furthermore, the forecasts obtained are used to analyze the possibility of gaining extraordinary returns with regard to the Buy & Hold strategy, through negotiation systems with basic rules.